Antipyretic effect of mitragynine and crude methanolic extract of Mitragyna speciosa Korth. in mice - Salleh, Annas (Universiti Putra Malaysia Press, 2020)
Mitragyna speciose Korth., also known as ketum or kratom, is a tropical plant native to Southeast Asia. Mitragynine is its major active alkaloid. It is traditionally used as treatment for various conditions, including fever. The crude extract of M. speciosa leaves has been proven to have anti-inflammatory and analgesic properties. In general, M. speciosa induces a dose-dependent effect, inducing a stimulant effect at low dose and an opioid-like effect at a high dose. This study was conducted to determine the antipyretic effect of mitragynine and methanolic extract of M. speciosa (MSM) using mice as an in vivo pyretic model. Eighty mice were divided into 8 groups: 6 treatment groups (mitragynine: 5, 10, and 20 mg/kg; MSM: 50, 100, and 200 mg/kg) and 2 control groups (20% Tween 80 in 0.9% NaCl; ketoprofen 1 mg/kg). Eighteen hours after induction of pyrexia by inoculation of yeast, rectal temperature was measured every half an hour for 5 hours. Compared to the negative control group, all groups treated with either mitragynine or MSM had significant reduction of rectal temperature at different points of time. The positive control group treated with ketoprofen had significant (P < 0.001) reduction of pyrexia from 0.5 to 5.0 hours after dosing. At 200 mg/kg, MSM has led to the opioid-like effect of hypothermia, possibly due to its synergistic effect with other compounds such as 7-hydroxymitragynine or mitragynine pseudoindoxyl. This article discusses concerns pertaining to toxicity of mitragynine and MSM, and possible involvement of cyclooxygenase and microsomal prostaglandin E2 synthase pathways. In conclusion, mitragynine and MSM possess dose-dependent antipyretic properties in mice.